Pengaruh Kualitas Pelayanan terhadap Kepuasan Penumpang Maskapai Penerbangan Batik Air di Yogyakarta International Airport Proposal Penelitian - Nadiya Arifiyanti Ananda Putri (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study focuses on the impact of service quality on the satisfaction of Batik Air passengers at Yogyakarta International Airport. The purpose of this study was to determine the impact and impact of service quality on passenger satisfaction. The method used is a quantitative method, which means using a calculation technique to determine the influence between the service quality of Batik Air airlines. Survey data is in the form of numbers and the analysis uses statistics, so this method is known as the quantitative or positivist method. Used to study a particular population or sample, the data sampling technique is carried out using a targeted sampling approach and is intended to test the proposed hypothesis using a research Data analysis is quantitative. The results showed that the significant value was P : 0.000, which means it is smaller than the 0.05 significance level (α). This means that passenger satisfaction at Batik Air in Indonesia has a great influence between Yogyakarta International Airport services. Keywords: service quality, pre-flight and passenger satisfaction